Sustainability in America's cities : (Island Press, 2011)
Sustainability is more than the latest "green" buzzword. It represents a new way of viewing the interactions of human society and the natural world. Sustainability in America's Cities highlights how America's largest cities are acting to develop sustainable solutions to conflicts between development and environment